RANCANG BANGUN MESIN PENCETAK BRIKET ARANG TEMPURUNG KELAPA - Aldo Firnando; Bayu Anggara; Edwin Aldrin; Pristiansyah; Haritsah Amrullah, Muhammad (Prosiding Seminar Nasional Inovasi Teknologi Terapan, 2024)
Charcoal briquettes are charcoal sticks made from coconut shells and molded using a machine to produce very high heat and can burn for a long time. The use of charcoal briquettes from coconut shells will contribute to reducing dependence on firewood, LPG gas and kerosene, the availability of which is running low and cannot be renewed, especially for communities in several Sungailiat areas and at the same time can support the use of coconut shell waste as a material. burn.This research aims to design and build a Coconut Shell Charcoal Briquette Printing Machine with a capacity of 12kg/hour and design a maintenance system for the Coconut Shell Charcoal Briquette Printing Machine so that it is ready for use and extends its service life. The design method used in this research is Verein Deutsche Ingenieuer (VDI 2222).The results of research on the Coconut Charcoal Briquette Printing Machine using the VDI 2222 design method, namely printing Coconut Charcoal Briquettes with a length of 60cm and a capacity of 12kg/hour. The maintenance system on this machine uses planned maintenance and inspections for operators to carry out independent maintenance.